Adverse Reactions to Intravenous Immunoglobulin Therapy: An Analysis of the Russian National Pharmacovigilance Database - A. V. Nechaev; S. A. Leshina; A. G. Klepikova; L. A. Gaiderova; O. G. Kornilova; N. Yu. Velts; K. V. Gorelov; V. A. Polivanov (Безопасность и риск фармакотерапии, 2024)
INTRODUCTION. Human immunoglobulins have been successfully used in clinical practice to treat multiple autoimmune and inflammatory conditions, and most of the current immunoglobulins are well tolerated by patients. However, patients may develop complications associated with proteins and other components of human plasma present in immunoglobulin products. The improvement of measures to ensure the quality, efficacy, and safety of immunobiologicals, including intravenous immunoglobulins (IVIGs), requires regular monitoring of data on individual and class-related adverse drug reactions (ADRs) associated with these medicinal products.AIM. This study aimed to conduct a systematic and comprehensive assessment of information on the potential ADRs to the IVIGs of Russian marketing authorisation holders from summaries of medicinal product characteristics (SmPCs) and the Russian national pharmacovigilance database.MATERIALS AND  METHODS.  The  study  analysed  the  SmPCs  of  all  the  IVIGs  authorised  for  use  in  Russia and the spontaneous reports of ADRs to the IVIGs of Russian marketing authorisation holders. The study was limited to the spontaneous reports submitted to the database PHARMACOVIGILANCE/MONITORING OF CLINICAL TRIALS OF MEDICINES in the Automated Information System of the Federal Service for Surveillance in Healthcare from 1 January 2020 to 30 August 2024.RESULTS. At the time of the study, there were 20 normal human IVIGs authorised in Russia, and Russian companies held marketing authorisations for 9 of these IVIGs. During the study period, there were 133 cases of ADRs associated with the IVIGs of Russian marketing authorisation holders. The most common ADRs included 41 (16.5%) cases of hyperthermia, 14 (5.6%) cases of headache, 14 (5.6%) cases of urticaria, and 14 (5.6%) cases of treatment ineffectiveness. The majority of these cases (70%) occurred when IVIGs were used for approved indications.CONCLUSIONS. All the ADRs identified in the analysis of the Russian national pharmacovigilance database were expected and consistent with the ADRs labelled in the SmPCs of the reported IVIGs. To reduce the risk of ADRs and improve the safety of IVIG therapy, it is required to develop a comprehensive approach to human IVIGs with quality assurance measures and standard use guidelines.